Effect of residual pore structure on the performance of TRISO particle fuel - Liu, Shichao; Li, Yuanming; Chen, Ping; Zhou, Yi; Tang, Changbing (Frontiers in Materials, 2023)
The thermal-mechanical performance of tri-isotropic (TRISO) particle with residual pore used in Light Water Reactor (LWR) was investigated. The effect of residual pore structure on the stress distribution of inner dense pyrolytic carbon (IPyC) layer, SiC layer and outer dense pyrolytic carbon (OPyC) layer was studied. The dimensional changes and fission gas release of the fuel particle layers were calculated. Residual pore on the SiC layer can affect the stress distribution of coated layers obviously. The residual pore especially the tetrahedron one may be the source of cracks on the SiC layer, which can break or loss the capacity of SiC layer. Residual pore has little influence on the stress distribution of the IPyC and OPyC layer.